Breast cancer mortality in Copenhagen after introduction of mammography screening: cohort study. Issue 7485 (13th January 2005) - Olsen, Anne Helene; Njor, Sisse H; Vejborg, Ilse; Schwartz, Walter; Dalgaard, Peter; Jensen, Maj-Britt; Tange, Ulla Brix; Blichert-Toft, Mogens; Rank, Fritz; Mouridsen, Henning; Lynge, Elsebeth
Abstract: Objectives To evaluate the effect on breast cancer mortality during the first 10 years of the mammography service screening programme that was introduced in Copenhagen in 1991. Design Cohort study. Setting The mammography service screening programme in Copenhagen, Denmark. Participants All women ever invited to mammography screening in the first 10 years of the programme. Historical, national, and historical national control groups were used. Main outcome measures The main outcome measure was breast cancer mortality. We compared breast cancer mortality in the study group with rates in the control groups, adjusting for age, time period, and region. Results Breast cancer mortality in the screening period was reduced by 25% (relative risk 0.75, 95% confidence interval 0.63 to 0.89) compared with what we would expect in the absence of screening. For women actually participating in screening, breast cancer mortality was reduced by 37%. Conclusions In the Copenhagen programme, breast cancer mortality was reduced without severe negative side effects for the participants.